1996
DOI: 10.1007/s004390050168
|View full text |Cite
|
Sign up to set email alerts
|

High parental age is associated with sporadic hereditary retinoblastoma: the Dutch retinoblastoma register 1862-1994

Abstract: We wished to determine the influence of parental age at the birth of a retinoblastoma patient on the risk of sporadic hereditary retinoblastoma. The parental age at birth of 941 patients of the Dutch retinoblastoma register was identified and compared between sporadic hereditary and nonhereditary patients. In a subcohort , a comparison was made with parental age at birth in the general population, as obtained from the Central Bureau of Statistics. Missing birth dates of the parents of retinoblastoma patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 23 publications
(36 reference statements)
3
30
1
1
Order By: Relevance
“…In our study, new germline mutations arose from fathers who were, on average, no older than fathers of children with maternally derived germline mutations or somatic initial mutations. Other, more formal studies of this issue involving greater numbers of cases have found a small paternal age effect (Vogel and Rathenberg 1975;der Kinderen et al 1990;Moll et al 1996), but at least two studies have not (Matsunaga et al 1990;Sasaki et al 1991). Additional research will probably be necessary to resolve this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, new germline mutations arose from fathers who were, on average, no older than fathers of children with maternally derived germline mutations or somatic initial mutations. Other, more formal studies of this issue involving greater numbers of cases have found a small paternal age effect (Vogel and Rathenberg 1975;der Kinderen et al 1990;Moll et al 1996), but at least two studies have not (Matsunaga et al 1990;Sasaki et al 1991). Additional research will probably be necessary to resolve this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, children of older fathers are not only more likely to have several diseases of clear genetic cause (Kühnert and Nieschlag, 2004;Lambert et al, 2006), they show also an increased risk for multifactorial diseases such as birth defects (Olshan et al, 1994;McIntosh et al, 1995;Kazaura et al, 2004;Bille et al, 2005;Zhu et al, 2005a, b;Archer et al, 2007;Yang et al, 2007), childhood cancers (Moll et al, 1996;Hemminki et al, 1999;Sharpe et al, 1999;Murray et al, 2002;Yip et al, 2006), prostate cancer (Zhang et al, 1999), breast cancer (controversial) (Colditz et al, 1991;Choi et al, 2005), diabetes mellitus type l (Bingley et al, 2000;Cardwell et al, 2005), multiple sclerosis (Montgomery et al, 2004), some forms of cerebral palsy (Fletcher and Foley, 1993), schizophrenia (Malaspina, 2001), bipolar disorder (Frans et al, 2008), autism (Reichenberg et al, 2006), epilepsy (Vestergaard et al, 2005), Alzheimer disease (Whalley et al, 1995) and lower intelligence quotients (Malaspina et al, 2005;Saha et al, 2009). However, some of the reported associations need to be considered with caution for methodological reasons in the statistical analysis, especially in regard to the validity of the data sources (Kirby, 2007) (Fig.…”
Section: Paternal Age and Outcome Of Offspringmentioning
confidence: 99%
“…[1][2][3][4][5] Patients with retinoblastoma during early childhood are at risk of developing osteosarcoma during adolescence, [6][7][8] and, as radiotherapy is frequently used for the treatment of retinoblastoma, a high proportion of osteosarcomas are observed within the radiation field. [6][7][8] Most cases of osteosarcoma occurring in retinoblastoma survivors are either bilateral or associated with a familial predisposition, i.e. in subjects presumably heterozygous for an RB1 gene germline mutation.…”
mentioning
confidence: 99%